Risk of female athlete triad development in Japanese collegiate athletes is related to sport type and competitive level - Sawai A (International Journal of Women's Health, 2018)
Akemi Sawai,1,* Bryan J Mathis,2,* Hiroaki Natsui,3 Alexander Zaboronok,2 Risa Mitsuhashi,1 Yuki Warashina,4 Noboru Mesaki,4 Hitoshi Shiraki,4 Koichi Watanabe4 1Graduate School of Comprehensive Human Sciences, University of Tsukuba, Tsukuba, Ibaraki, Japan; 2Faculty of Medicine, University of Tsukuba, Tsukuba, Ibaraki, Japan; 3Faculty of Sports and Health Sciences, Japan Women’s College of Physical Education, Setagaya-ku, Tokyo, Japan; 4Faculty of Health and Sport Sciences, University of Tsukuba, Tsukuba, Ibaraki, Japan *These authors contributed equally to this work Introduction: Menstrual dysfunction, musculoskeletal injury, and poor nutrition combine to form the female athlete triad (FAT), which results in serious health consequences for affected athletes. To this point, the risk factors of this phenomenon have not been fully explored in Japanese female college athletes. Additionally, the effect of competitive level on FAT risk factors has also not been reported. Therefore, we aimed to examine FAT risk factors in Japanese female athletes of various sports as well as examine the impact of competitive level on FAT.Methods: A Japanese-language survey was completed by 531 athletes and 20 nonathletes at two Japanese universities and answers with regard to menstrual status, musculoskeletal injury, nutrition, and other variables were analyzed based on classification of the sports into nine distinct groups based on activity type. Sport intensity, training volume, and competitive levels were used to further classify each sport. One-way ANOVA and the Bonferroni post hoc test using SPSS were carried out to analyze significance for relationships between sport intensity and FAT risk factors. Additionally, the relationship between competitive level and FAT risk factors was analyzed by ANOVA and Bonferroni post hoc tests.Results: Sport intensity was positively correlated with a delay in menarche as well as dysmenorrhea and poor nutrition while musculoskeletal injury was correlated with repetitive, high-training volume sports. Lower competitive levels increased dysmenorrhea but did not impact injury status or nutrition.Conclusion: Sport intensity and training volume, but not competitive level, are the critical factors affecting FAT risk in Japanese female college athletes. Keywords: athletes, dysmenorrhea, FAT, female, Japanese, triad